A foliar disease model for use in wheat disease management decision support systems. - Audsley, Eric; Milne, Alice E.; Paveley, Neil (Blackwell Publishing Ltd., 2005)
A model of winter wheat foliar disease is described, parameterised and tested for Septoria tritici (leaf blotch), Puccinia striiformis (yellow rust), Erysiphe graminis (powdery mildew) and Puccinia triticina (brown rust). The model estimates diseaseinduced green area loss, and can be coupled with a wheat canopy model, in order to estimate remaining light intercepting green tissue, and hence the capacity for resource capture. The model differs from those reported by other workers in three respects. Firstly, variables (such as weather, host resistance and inoculum pressure) which affect disease risk are integrated in their effect on disease progress. The agronomic and meteorological data called for are restricted to those commonly available to growers by their own observations and from meteorological service networks. Secondly, field observations during the growing season can be used both to correct current estimates of disease severity and modify parameters which determine predicted severity. Thirdly, pathogen growth and symptom expression are modeled to allow the effects of fungicides to be accounted for as protectant activity (reducing infections which occur postapplication) and eradicant activity (reducing growth of pre-symptomatic infections). The model was tested against data from a wide range of sites and varieties, and was shown to predict the expected level of disease sufficiently accurately to support fungicide treatment decisions.
Keywords: winter wheat; foliar diseases; weather; disease observations